2019
DOI: 10.1111/nyas.14172
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical findings on the potential of intranasal neuropeptide Y for treating hyperarousal features of PTSD

Abstract: Acoustic startle response (ASR) assesses hyperarousal, a core symptom of posttraumatic stress disorder (PTSD). Intranasal neuropeptide Y (NPY) administration was shown to prevent hyperarousal in single prolonged stress (SPS) rodent PTSD model. However, it is unclear how ASR itself alters responses to stress. Rats (A-S-A) were exposed to acoustic startle (AS) 1 day before SPS (ASR1) and 2 weeks afterward (ASR2). Other groups were exposed in parallel to either AS (A-A) or SPS or neither. SPS enhanced ASR2. In re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The majority of animal models for PTSD, including the Single Prolonged Stress (SPS) paradigm, have been studied predominantly with males. The SPS model elicits many stress-associated maladaptive behaviors relevant to PTSD, such as anxiety, depression, hyperarousal, impaired social interaction, and impaired fear memory extinction, as well as molecular changes including dysregulation of the HPA axis and activation of the noradrenergic system (Liberzon et al, 1997 ; Khan and Liberzon, 2004 ; Kohda et al, 2007 ; Knox et al, 2012 ; Eagle et al, 2013 ; Keller et al, 2015b ; Liu et al, 2016 ; Souza et al, 2017 ; Lisieski et al, 2018 ; Nwokafor et al, 2019b ; Serova et al, 2019 ; Mancini et al, 2020 ). Particularly in the locus coeruleus, the major source for norepinephrine in the brain, SPS induced gene expression of key stress-related enzymes and receptors (Serova et al, 2013b , 2019 ; Sabban et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of animal models for PTSD, including the Single Prolonged Stress (SPS) paradigm, have been studied predominantly with males. The SPS model elicits many stress-associated maladaptive behaviors relevant to PTSD, such as anxiety, depression, hyperarousal, impaired social interaction, and impaired fear memory extinction, as well as molecular changes including dysregulation of the HPA axis and activation of the noradrenergic system (Liberzon et al, 1997 ; Khan and Liberzon, 2004 ; Kohda et al, 2007 ; Knox et al, 2012 ; Eagle et al, 2013 ; Keller et al, 2015b ; Liu et al, 2016 ; Souza et al, 2017 ; Lisieski et al, 2018 ; Nwokafor et al, 2019b ; Serova et al, 2019 ; Mancini et al, 2020 ). Particularly in the locus coeruleus, the major source for norepinephrine in the brain, SPS induced gene expression of key stress-related enzymes and receptors (Serova et al, 2013b , 2019 ; Sabban et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since hyperarousal is associated with activation of the NE/LC system (Naegeli et al, 2018 ) and is elevated in PTSD (O’Donnell et al, 2004 ) as well as by SPS (Serova et al, 2013 ; Nwokafor et al, 2019 ), we examined the relationship between SPS triggered changes in acoustic startle response (ASR) and NET gene expression in the LC (Experiment 3). For this experiment, basal ASR (ASR1) was determined, and one group was exposed to SPS and the other remained unstressed.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperarousal was assessed by deviation from the basal Acoustic Startle Response (ASR1). ASR was measured as previously described (Nwokafor et al, 2019 ) in a sound-proof chamber (SR-LAB; San Diego Instruments, San Diego, CA, USA). The piezoelectric accelerometer was calibrated using a stabilimeter for reliable and consistent sensitivity among the chambers.…”
Section: Methodsmentioning
confidence: 99%
“…With a further delay of 2 weeks post-SPS before initiating treatment with IN-NPY, the proportion of mice displaying severe anxiety (as assessed by elevated plus maze) also increased from 17.5% to 57.1% (indicative of delayed onset/worsening progression of the PTSD-like induced phenotype) and only a higher dose of 300 µg was able to effectively reverse elevated anxiety, depressive-like, and hyperarousal behaviors [ 128 ]. However, further testing another 7 days post-NPY revealed that the therapeutic benefit of IN-NPY lasted only 7 days, but that a second IN-NPY dose sustained NPY’s neuroprotective role [ 129 ]. Intranasal administration of NPY receptor subtype 1 (Y1R) and 2 (Y2R) agonists to stressed rats revealed that these resiliency effects are dependent on NPY receptor subtype 1 [ 130 ].…”
Section: Npymentioning
confidence: 99%